2018
DOI: 10.21608/ejmm.2018.285331
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Surgical Site Infection in General Surgery Department at Sohag University Hospital

Abstract: Background: Surgical site infections (SSI) are the most common nosocomial infections in surgical patients and lead to prolonged hospital stay, readmission to the hospital, and increased morbidity and mortality. Objectives: This study aimed to detect the incidence of SSI and the risk factors, the causative organisms and their antimicrobial susceptibility pattern in general surgery department at Sohag university hospital. Methodology: A prospective SSI surveillance at Sohag University hospital from (January 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
2
2
0
Order By: Relevance
“…In our study percentage of MRSA causing SSI was 20%, matching with the results of Esmat et al in Sohag, who found that Staphylococcus aureus was responsible for 20% of SSIs; all of which were MRSA 22 . In many American and European hospitals, the percentage of MRSA has ranged from 29% to 35%; while in India it ranged from 30% to 87% 23,24 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study percentage of MRSA causing SSI was 20%, matching with the results of Esmat et al in Sohag, who found that Staphylococcus aureus was responsible for 20% of SSIs; all of which were MRSA 22 . In many American and European hospitals, the percentage of MRSA has ranged from 29% to 35%; while in India it ranged from 30% to 87% 23,24 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to a previous study by Srinivasan et al, who reported 80% of MRSA isolates from surgical wards. 17 The MRSA isolated from surgery in this investigation was 27.8%, which corresponds to the findings of Esmat et al, 18 19 As per the latest annual report of INSAR, multidrug resistance among MRSA strains was very common and variable between different centers. 91.8% of isolates were resistant to ciprofloxacin, followed by 75% to erythromycin, 39.2% to cotrimoxazole, 35.8% to clindamycin, and 15.1% to tetracycline.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies had reported the increased incidence of MDR in health care associated infections. 31,32 And there are much evidence that hospitalized patients who are colonized or infected with antibiotic resistant organisms can shed these organisms into environment, which becomes a reservoir for subsequent transmission. 33 Dancer highlighted on 2014 the association between HAI rates and environmental bioburden.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 660 samples were collected in the current study in the three times of evaluation; 220 samples in each time: Seventy swabs from ORs surfaces were collected from 9 sites; [operating table top surface (10), anesthesia machine surface (10), instruments trolley (8), electro cautery machine (5), sterilizing hand gel pumps (7), the laryngoscope handles (7), Doors handles (12), diathermy (DC) machine surface (6), and electric power switch (5)] One hundred twenty three swabs from other SWs surfaces: 42 swabs from urology department ,39 swabs from orthopedics , 26 swabs from general surgery and 16 swabs from gynecology department, these samples were collected from 6 sites: [Doors handles (11), bed side table's surface (28), bed linen (24), bed ledges and arms (31), curtains edges (15), and solutions holders (14)].…”
Section: Microbiological Assessmentmentioning
confidence: 99%